A Narrative Inquiry on Learners of Home-Based Exercise - Eson, Kezia Jeanette; Nillos, Charles; Guitche, Melona; Perez, Rexomar (Technium Social Sciences Journal, 2024)
Exercises performed at home are called Home-based Exercises. The suspension of classes exposed the learners to home-based exercises. The goal of this study is to explore the ideas and insights of learners on Home-based Exercise. The study utilized Basic Qualitative Research, specifically, Narrative Inquiry to gather the stories of learners. In a semi-structured interview, seven conversation partners participated. The seven conversation partners were chosen using inclusion criteria. The rigorous data analysis and data explication using Creswell’s six-step data explication elicited four central themes: (1) The Obstacle: Hindrances in Performing Home-based Exercise, (2) The Push: A way to overcome the Hindrances, (3) The Goal: An Exercise Plan, and (4) The Drive: A motivation to keep going. The findings of this study provided a picture of how learners have coped with the challenges posed by exercising at home. This study carries meaningful data as a reference for future innovation in Home-based Exercise.